13th World Congress of Food Science &Amp; Technology 2006
DOI: 10.1051/iufost:20060688
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining a cold chain in retail: does it work?

Abstract: A survey of the retail in Ljubljana, the capital city of Slovenia regarding the maintenance of a cold chain is presented now, when HACCP is mandatory for three years already (since January 1 st 2003). The objectives were: to analyze the situation of maintaining a cold chain in retail and to find out handling of selected perishable foodstuffs in stores. We compared the results with the findings from our first research in this field in 2002 when HACCP was not yet mandatory. In both researches we confirmed that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Food-borne illnesses mentioned by Mead et al (1999) affect millions of people each year, and an unknown but sizeable proportion of these illnesses could be prevented through actions taken by consumers (Medeiros et al, 2004). A lot of attention on the maintenance of a cold chain is focused on certain parts of the food chain (from farmer or producer to the retailer), but temperature measurements taken in stores (Jevšnik, Ovca, & Likar, 2006; clearly show that the cold chain is frequently broken. The findings of James, Evans, and James (2008) and many other studies show that domestic refrigerators throughout the world operate above the recommended temperatures and are not properly maintained (Johnson et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Food-borne illnesses mentioned by Mead et al (1999) affect millions of people each year, and an unknown but sizeable proportion of these illnesses could be prevented through actions taken by consumers (Medeiros et al, 2004). A lot of attention on the maintenance of a cold chain is focused on certain parts of the food chain (from farmer or producer to the retailer), but temperature measurements taken in stores (Jevšnik, Ovca, & Likar, 2006; clearly show that the cold chain is frequently broken. The findings of James, Evans, and James (2008) and many other studies show that domestic refrigerators throughout the world operate above the recommended temperatures and are not properly maintained (Johnson et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, non-conformities in cleanliness occurred in facilities out of the sight of the consumers, such as the storage rooms, the facilities for the handling of slicing meat, and the cleaning equipment rooms [22]. Another study indicated that the retailers were unaware of the importance of maintaining the cold chain and, combined, with the lack of a control system during storage in stores, temperatures were not recorded [42]. In the present study, the frequent phenomenon was that the stores stored "Spoiled food products/products for return" beneath the fresh ones in the same refrigerator (Figure 3B).…”
Section: Discussionmentioning
confidence: 97%
“…The temperature distributions recorded in this study appear to have high variability in most of the checked refrigerators. In many cases, the periodic increase in temperatures is probably due to the defrosting system of the refrigerators [34,42]. Other factors that cause high variability in product temperatures are the influence of lighting and nearby standing customers, as well as the interruptions of the cold chain by resupplying the refrigerators [42].…”
Section: Discussionmentioning
confidence: 99%